(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Labour is one of the primary factors of production. It is considered to be important not only because it is productive but also because it activates other factors and makes them useful for production purposes. Agricultural labourers, mostly landless constitute the poorest segment of the Indian agricultural population. They belong to the economically backward and oppressed section of the society. Rural women often manage complex households and pursue multiple livelihood strategies. Their activities typically include producing agricultural crops, tending animals, processing and preparing food, working for wages in agricultural or other rural enterprises, collecting fuel and water, engaging in trade and marketing, caring for family members and maintaining their homes. The international development community has recognized that agriculture is an engine of growth and poverty reduction in countries where it is the main occupation of the poor. But the agricultural sector in many developing countries is underperforming, in part because women, who represent a crucial resource in agriculture and the rural economy through their roles as farmers, labourers and entrepreneurs, almost everywhere face more severe constraints than men in access to productive resources. The present work is focused on agricultural labour’s contribution to build strong rural setup with individual improvement, hence it has considered the Hassan district to do study.